(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Xylanases are important hydrolytic enzymes responsible for the degradation of xylan, the major hemicellulosic component of lignocellulosic biomass. These enzymes play an essential role in various industrial processes, including pulp and paper bleaching, food processing, textile manufacturing, animal feed formulation, and biofuel production. However, the high cost of enzyme production has limited their widespread industrial application. One promising approach to reducing production costs is the utilization of inexpensive lignocellulosic biomass as a fermentation substrate. The present investigation focuses on the production of extracellular xylanase by the white-rot fungus Ganoderma lucidum using hydrolysates derived from widely growing non-food plant biomass. Six terrestrial and aquatic weeds—Commelina benghalensis, Cynodon dactylon, Eichhornia crassipes, Parthenium hysterophorus, Pistia stratiotes, and Setaria viridis—were evaluated as potential substrates for xylanase production under submerged fermentation conditions. Plant biomass samples were subjected to autohydrolysis to release hemicellulose-rich soluble compounds that could serve as carbon sources for fungal growth and enzyme production. Fermentation experiments were conducted at 25 ± 2 °C and pH 5.5 under static conditions for 7–14 days. Among the substrates tested, hydrolysate derived from Setaria viridis resulted in the highest xylanase production, followed by Cynodon dactylon and Parthenium hysterophorus. Moderate enzyme activity was observed with aquatic plant substrates such as Eichhornia crassipes and Pistia stratiotes, whereas Commelina benghalensis supported minimal enzyme production. The results demonstrate that non-food plant biomass can serve as an economical and sustainable substrate for xylanase production. Utilization of such biomass not only reduces production costs but also contributes to effective management of invasive plant species and lignocellulosic waste. This study highlights the potential of Ganoderma lucidum as a promising organism for cost-effective industrial enzyme production.